Lipodermatosclerosis as a potential complication of chronic venous insufficiency - A. K. Blbulyan; K. K. Arustamyan; L. K. Manukyan; S. A. Minasyan; G. A. Gomtsyan (Акушерство, гинекология и репродукция, 2025)
Pregnancy and childbirth in women with varicose vein disease (VVD) are typically associated with a high risk of developing thrombotic, obstetric and fetal complications. Lipodermatosclerosis (LDS) is one of the less common complications related to chronic venous insufficiency (CVI). This article presents a clinical case where LDS developed during late-stage pregnancy (35–36 weeks) as a complication of pre-existing VVD, which is noteworthy due to the rarity of such condition that demonstrates relevant diagnostic challenges particularly during pregnancy. Enhancing the effectiveness of a multidisciplinary approach is essential for diagnosing rare VVD complications in pregnant women.